ANALISIS PENGELOLAAN KAS PADA CV ILLUN MAJU PAPUA - Try Julianty Mangngayun; Longginus Gelatan (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2025)
This study aims to analyze the optimal cash amount that should be held by CV Illun Maju Papua and cash management for fulfilling short-term obligations by analyzing data using the Miller-Orr model and cash ratio. The method used is a descriptive method with a quantitative approach. Data collection techniques include observation, interviews, and documentation. The results of the study indicate that the optimal cash amount the company should hold is IDR 171,372,981, and the ability to meet short-term obligations is classified as good, although experiencing a decreasing trend.